Detection of Protein Aggregates in Brain and Cerebrospinal Fluid Derived from Multiple Sclerosis Patients - David, Monique Antoinette; Tayebi, Mourad (Frontiers in Neurology, 2014)
Studies of the properties of soluble oligomers species of amyloidogenic proteins, derived from different proteins with little sequence homology, have indicated that they share a common structure and may share similar pathogenic mechanisms. Amyloid β, tau protein as well as amyloid precursor protein normally associated with Alzheimer’s disease and Parkinson’s disease were found in lesions and plaques of Multiple Sclerosis patients. The Objective of the study is to investigate whether brain and CSF samples derived from Multiple Sclerosis patients demonstrate the presence of soluble oligomers normally associated with protein misfolding diseases such as Alzheimer’s disease. We have used anti-oligomer monoclonal antibodies to immunodetect soluble oligomers in CSF and brain tissues derived from Multiple Sclerosis patients. In this report, we describe the presence of soluble oligomers in the brain tissue and cerebral spinal fluid of Multiple Sclerosis patients detected with our monoclonal anti-oligomer antibodies with Western blot. These results might suggest that protein aggregation plays a role in Multiple Sclerosis pathogenesis although further and more refined studies are needed to confirm the role of soluble aggregates in Multiple Sclerosis.